Growing into and out of Social Conflict - Philipp Harms; Stefan Zink (Swiss National Bank, Study Center Gerzensee, 2002)
We present a model of growth and distributional conflict that implies a non-monotonic relationship between average wealth and the likelihood of radical redistribution: while the net benefits of redistribution for members of the poor class are small at low stages of development, a shift towards egalitarianism considerably improves agents' income prospects once an intermediate level of per-capita wealth is reached. As the economy grows further, the incentive to challenge the existing social order decreases again and eventually vanishes. This nonmonotonicity captures the observation that historical shifts to radically redistributive policies frequently took place after extended periods of economic growth.
Keywords: P16; O11; D31; D74; 330; Political economy; inequality; borrowing constraints; redistribution; revolution; Kuznets curve; Verteilungskonflikt; Verteilungstheorie; Kuznets-Kurve; Theorie